Long‐term maintenance of HepaRG cells in serum‐free conditions and application in a repeated dose study. Issue 10 (30th September 2013) - Klein, Sebastian; Mueller, Daniel; Schevchenko, Valery; Noor, Fozia
ABSTRACT: Chronic repeated‐dose toxicity studies are still carried out on animals and often do not correlate with the effects in human beings mainly due to species‐specific differences in biotransformation. The human hepatoma cell line HepaRG has been used for human relevant toxicity assessment. However, HepaRG cells are commonly maintained in serum containing medium which limits their use in 'omics'‐based toxicology. In this study, we compared the maintenance of HepaRG cells in standard serum‐supplemented and serum‐free conditions. Viability and Cytochrome P450 (CYP) activity during long‐term cultivation were assessed. Liver‐specific albumin and urea production was measured. The extracellular metabolome (amino acids, glucose, lactate and pyruvate) was measured to compare different cultivation conditions using metabolic flux analysis. Although metabolic flux analysis reveals differences in certain parts of the metabolism, e.g. production of urea, the overall metabolism of serum‐free and serum‐supplemented cultured HepaRG cells is similar. We conclude that HepaRG cells can be maintained in optimized serum‐free conditions for 30 days without viability change and with high CYP activity. We also tested the acute (24 h) and long‐term repeated‐dose (7 doses, every second day) toxicity of valproic acid. We calculated an EC50 value of 1.4 mM after repeated exposure which is close to the cmax value for valproic acid. Maintenance of HepaRG cells in serum‐free conditions opens up the opportunity for the use of these cells in human long‐term repeated‐dose hepatotoxicity studies and for application in systems toxicology. Copyright © 2013 John Wiley & Sons, Ltd. Abstract : HepaRG cells were maintained viable with constant CYP activities and liver‐specific functions for 30 days in serum‐free medium (SFM). The long‐term viability and CYP activities were superior to those reported for primary human hepatocytes in vitro . Metabolic flux analysis indicates that the central carbon metabolism in SFM is comparable to standard conditions. This system can be applied for repeated dose toxicity assessments and will pave way for application on high content 'omics' platform in systems toxicology.